ITC EUREST-PLUS Spain: protocol of a prospective longitudinal study of smokers in Spain - Marcela Fu; Yolanda Castellano; Olena Tigova; Pete Driezen; Mary E. Thompson; Susan C. Kaai; Anne C.K. Quah; Geoffrey T. Fong; Constantine I. Vardavas; Esteve Fernández (Elsevier, 2023)
Objective: The ITC EUREST-PLUS Spain Survey is a longitudinal study of a representative sample of Spanish adult (≥18 years old) smokers. This protocol describes the methods of the 2021 follow-up survey. Method: The ITC EUREST-PLUS Survey, a prospective cohort study of a representative sample of smokers in six European countries, was conducted in 2016 (baseline) and 2018 (waves 1 and 2). The 2021 ITC EUREST-PLUS Spain Survey is a continuation of the Spanish cohort with a new interview in 2021 (wave 3). Lost participants were replaced with new smokers recruited using the same multi-stage sampling design. This latest follow-up aims to examine current patterns and transitions of tobacco use and to evaluate the impact of new tobacco-related policies. Comments: The ITC EUREST-PLUS Spain Survey will provide recent information about the impact of tobacco control policies on smoking behaviour. Resumen: Objetivo: La encuesta ITC EUREST-PLUS España es un estudio longitudinal de una muestra representativa de fumadores adultos (≥18 años) españoles. Este protocolo describe los métodos de la encuesta de seguimiento de 2021. Método: La encuesta ITC EUREST-PLUS, un estudio de cohortes prospectivo de una muestra representativa de fumadores en seis países europeos, se realizó en 2016 y 2018 (olas 1 y 2). La encuesta ITC EUREST-PLUS España de 2021 es una continuación de la cohorte española con una nueva entrevista en 2021 (ola 3). Se sustituyeron las pérdidas con nuevos fumadores reclutados usando el mismo diseño muestral multietápico. Este último seguimiento pretende examinar los patrones actuales y las transiciones del uso de tabaco, y evaluar el impacto de nuevas políticas relacionadas con el tabaco. Comentarios: La encuesta ITC EUREST-PLUS España de 2021 proporcionará información reciente sobre el impacto de las políticas de control del tabaco en el consumo de tabaco.